2004
DOI: 10.1249/01.mss.0000135791.27929.c1
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscle Strength and Disability Level of Low Back Pain in Collegiate Wrestlers

Abstract: The relatively low strength of trunk extensors may be one of the factors related to nonspecific chronic low back pain in collegiate wrestlers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 26 publications
3
55
1
5
Order By: Relevance
“…1,6 It can be assumed that, in cases of postural instability, the insufficient stabilizers must be compensated by other muscles. A significant decrease in strength of trunk muscles, especially the extensors, in patients with low back pain has been established, 8,23,34,37,38 suggesting that strengthening exercises of the trunk muscles may be an optimal rehabilitation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…1,6 It can be assumed that, in cases of postural instability, the insufficient stabilizers must be compensated by other muscles. A significant decrease in strength of trunk muscles, especially the extensors, in patients with low back pain has been established, 8,23,34,37,38 suggesting that strengthening exercises of the trunk muscles may be an optimal rehabilitation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In wrestlers, the prevalence of nsLBP in athletes with and without LRA has been reported to be 40% and 44%, demonstrating no specific association between nsLBP and LRA. 12 Authors of previous studies reported that individuals without nsLBP had high prevalence of LRA (general population, 32% 26 ; wrestlers, 70% 12 ). To date, there has been no report that has examined the possible association between nsLBP and LRA in judo athletes.…”
mentioning
confidence: 99%
“…12,18 LRA can be detected using plain-film radiographs, computed tomography, 99m Tc-HMDP bone scans, and magnetic resonance imaging (MRI). Plain-film radiographs and MRI examinations are often used to identify LRA in athletes.…”
mentioning
confidence: 99%
See 2 more Smart Citations